1997
DOI: 10.1111/j.1346-8138.1997.tb02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Panniculitis Treated by a Combination Therapy of Hydroxychloroquine and Quinacrine

Abstract: Lupus erythematosus panniculitis (LEP) is an unusual clinical variant of lupus erythematosus (LE) in which the cutaneous inflammatory reaction occurs primarily in the deeper corium. The common clinical features of LEP includes asymptomatic, firm, sharply defined nodules. The histologic findings are characterized by nonspecific panniculitis composed of lymphoid cells, plasma cells, and histiocytes with varying degrees of necrobiotic changes with fibrinoid deposits. In our case, a 24-year-old male patient visite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…35 Some authors believe that HCQ is safer but less effective than CQ considering the well-known side-effects, such as irreversible retinopathy. [41][42][43] The results of the present study suggest that quinacrine is highly efficient in patients with CLE; however, only a low number of patients applying quinacrine were included in the study. 37 The results of the present analysis demonstrated a slightly higher efficacy of HCQ (86Á9%) compared with CQ (81Á5%) in all CLE subtypes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…35 Some authors believe that HCQ is safer but less effective than CQ considering the well-known side-effects, such as irreversible retinopathy. [41][42][43] The results of the present study suggest that quinacrine is highly efficient in patients with CLE; however, only a low number of patients applying quinacrine were included in the study. 37 The results of the present analysis demonstrated a slightly higher efficacy of HCQ (86Á9%) compared with CQ (81Á5%) in all CLE subtypes.…”
Section: Discussionmentioning
confidence: 76%
“…39 Moreover, a recently published prospective longitudinal cohort study of 128 patients with CLE, 40 as well as several case reports, confirmed that a combination of HCQ or CQ with quinacrine, respectively, is highly effective. [41][42][43] The results of the present study suggest that quinacrine is highly efficient in patients with CLE; however, only a low number of patients applying quinacrine were included in the study.…”
Section: Discussionmentioning
confidence: 76%
“…Several case reports have been published demonstrating that the combination therapy is highly efficient in patients with different subtypes of CLE (DLE, SCLE, and LE panniculitis). [92][93][94] Moreover, quinacrine (100 mg per day) was added in patients with SLE, who were maintained on prednisolone and hydroxychloroquine (some also on azathioprine). 95 Three months after the initiation of quinacrine treatment, disease activity measured by the SLE Disease Activity Index and anti-double-stranded DNA and anticardiolipin antibodies were reduced, followed by reduction or discontinuation of prednisolone in all patients and azathioprine in some patients.…”
Section: Dosage Of Quinacrinementioning
confidence: 99%
“…Of the 147 prescriptions for compounded quinacrine filled by our pharmacy, 93 were written by dermatologists. That most of the quinacrine prescriptions were written by dermatologists at our institution suggests that the practice of using combinations of antimalarials such as hydroxychloroquine and quinacrine 17,35 or chloroquine and quinacrine 36,37 in inflammatory disorders has not yet been fully adopted by our colleagues in rheumatology, internal medicine, and family medicine.…”
Section: Martindale: the Complete Drug Referencementioning
confidence: 99%